A study on the antibacterial efficacy of Halohydantoin-containing foams. Issue 5 (27th May 2022) - Nedelea, Andreea-Gabriela; Robins, Lori; Williams, Jeffrey; Maddocks, Sarah
Abstract : Heterocyclic N-halamine compounds such as 1-monochloro-5, 5-dimethylhydantoin (MCDMH) and 1, 3-dichlor-5, 5-dimethylhydantoin (DCDMH) show antimicrobial activity and odour control. Both MCDMH and DCDMH stabilise and display oxidative chlorine (Cl+1) and, in aqueous environments, generate hypochlorous acid (HOCl). It is well known that HOCl, produced by neutrophils as part of the respiratory immune response, is used as a defence mechanism against foreign bodies. This study aimed to investigate the antibacterial efficacy of proprietary foaming formulations containing mixtures of MCDMH and DCDMH provided by MedeSol Inc., as a potential delivery mechanism for HOCl. The efficacy of the foams containing active chlorine concentrations of 350 ppm and 1050 ppm was tested against single and multi-species bacterial mixtures of S. aureus, P. aeruginosa, E. coli, E. faecalisand K. pneumoniae. Cellulose filters were contaminated with single/multispecies bacterial suspensions and left to air-dry; the two foam concentrations were applied for 15, 30 and 60 seconds at a time. Samples were taken and the total viable count method was employed to determine antibacterial efficacy of the foams. Following the use of both foam concentrations, no colonies were recovered at any time-points in both single and multi-species experiments. In contrast, the negative controls where the foam application was omitted, resulted in high numbers of bacterial colonies. MCDMH-containing foams have very strong antibacterial potential as a result of active chlorine release. Further studies are needed to determine concentration dependence and use in other applications including hand sanitation.